Predictors of Unexpected Early Reocclusion After Successful Mechanical Thrombectomy in Acute Ischemic Stroke Patients. Issue 11 (November 2018) - Mosimann, Pascal J.; Kaesmacher, Johannes; Gautschi, Dominic; Bellwald, Sebastian; Panos, Leonidas; Piechowiak, Eike; Dobrocky, Tomas; Zibold, Felix; Mordasini, Pasquale; El-Koussy, Marwan; Wiest, Roland; Bervini, David; et al.
Abstract : Background and Purpose—: Sustained successful reperfusion is an important prognostic factor for good clinical outcome in acute ischemic stroke. We aimed to identify the prevalence, clinical impact, and predictors of early reocclusion after initially successful thrombectomies within a prospective cohort. Methods—: A total of 711 stroke patients with successful reperfusion (modified Thrombolysis in Cerebral Infarction, 2b/3) followed with magnetic resonance or computed tomographic angiography at 24 to 48 hours were included. Multivariable logistic regression analysis was used to evaluate associated factors and clinical impact. Results are displayed as adjusted odds ratio (aOR) and 95% CI. Improvement in accuracy of additional imaging findings on angiography control runs after the intervention was evaluated by area under the curve. Results—: Early reocclusion was observed in 16 of 711 successfully reperfused patients (2.3%; 95% CI, 1.1–3.3; median delay: 20 hours). Suggestive predictors were higher platelets on admission (aOR, 1.01; 95% CI, 1.01–1.02), prestroke functional dependence (aOR, 7.12; 95% CI, 1.49–34.03), and stroke of undetermined or other specified pathogenesis in the TOAST classification (aOR, 7.19; 95% CI, 1.10–47.05 and aOR, 36.50; 95% CI, 4.47–298.11, respectively). When implementing residual embolic fragments or stenosis at the thrombectomy site into the logistic regression model, discrimination between patients with and without reocclusion improved significantly (area under the curve, 0.955 versus 0.854; P =0.023). Early reocclusion was an independent predictor of unfavorable outcome at 90 days (aOR for modified Rankin Scale ⩽2, 0.13; 95% CI, 0.03–0.57). Conclusions—: Early reocclusion within 48 hours after successful mechanical thrombectomy is rare but associated with poor outcome. Patients with high platelets on admission and residual embolic fragments or stenosis at the thrombectomy site are at high risk for reocclusion, which may be prevented or corrected after carefully re-evaluating the last angiographic run. Abstract : Supplemental Digital Content is available in the text.